STRUCTURAL ANALYSIS OF INTRINSIC ELEMENTS IN THE FILM HOW TO MAKE A MILLION BEFORE GRANDMA DIES - Enzy Abdad Subardja; Nadya Fatikhur Rifqi; Safira Azahra Saragih; Fathimah Zahra; Talitha Aulia (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The film "How to Make a Million Before Grandma Dies" tells the emotional journey of a character who struggles to achieve wealth before his grandmother dies. The purpose of this research is to understand how various elements in the film such as plot, character, theme, and setting work together to creating an in-depth and touching experience. The research method in this study uses qualitative research by watching the film several times and noting every important detail. This process involves observing how the storyline develops, how the characters interact, and how the setting supports the film's themes This research analysis shows that this film is very successful in combining intrinsic elements to form a strong and heartfelt story. The language style used is also very effective in building an emotional connection between the audience and the characters in the film This film not only provides entertainment, but also offers deep reflections on life and human relationships. Through this analysis, we can see how strong this film is in conveying important messages, making it a compelling and meaningful experience for collaborative audiences to create an engaging and meaningful cinematic experience.